What girls need : how to raise bold, courageous, and resilient women - Porges, Marisa (Viking, an imprint of Penguin Random House LLC, 2020)
"A powerful book about how we can raise girls to become bold, ambitious women." --Adam Grant. A former White House strategist and fighter jet pilot now at the helm of one of the premier schools for girls in the country illuminates the ways parents and educators can support audacity and ambition in girls everywhere. What do girls really need to succeed? As a student at the all-girls Baldwin School outside of Philadelphia, Marisa Porges was raised in a community designed to produce strong, independent women. After earning a BA in geophysics from Harvard, she fulfilled her childhood dream of flying jets off aircraft carriers for the US Navy and served as a counterterrorism expert in Afghanistan and the Obama White House. In 2016, in an unexpected move for someone whose ambitions had taken her so far from home, Porges returned to head The Baldwin School. In doing so, she began to see with great clarity how small moments and turning points in her early education gave her the tools she would eventually sharpen and deploy to excel in areas that were traditionally perceived as being part of "a man's world." What Girls Need combines lessons Porges learned along her career path with the practices she and her colleagues are developing at The Baldwin School to help today's girls cultivate the skills and traits they need to become tomorrow's leading women. The traditional means of commanding a room have often been dubbed "unfeminine" and women of previous generations were pressured to behave like a man in order to win the day. But the ways we define leadership are changing, and the women now stepping into leadership roles are mapping new paths to inhabiting traits such as grit, resilience, audacity, and self-confidence. Porges is writing to prepare the next generation to confidently hold their own later in life in whatever fields they enter, whatever challenges they face, and to celebrate and own the ways that traits which might have been undervalued in the past--empathy, collaboration, and an evolving mind-set--can and will define the future's leaders"--